Unveiling the predictive power of biomarkers in traumatic brain injury: A narrative review focused on clinical outcomes - Liang, Sitao; Hu, Zihui (Biomedical papers, 2024)
Traumatic brain injury (TBI) has long-term consequences, including neurodegenerative disease risk. Current diagnostic tools are limited in detecting subtle brain damage. This review explores emerging biomarkers for TBI, including those related to neuronal injury, inflammation, EVs, and ncRNAs, evaluating their potential to predict clinical outcomes like mortality, recovery, and cognitive impairment. It addresses challenges and opportunities for implementing biomarkers in clinical practice, aiming to improve TBI diagnosis, prognosis, and treatment.
Keywords: traumatic brain injury; biomarkers; extracellular vesicles; non-coding RNAs; clinical outcomes